SOLVING OF PROBLEMS OF HEREDITY OF SMELTED CAST IRON AT ОАО “MINSK WORKS OF HEATING EQUIPMENT” - L. Z. Pisarenko; V. A. Hatskevich; D. V. Kuis (Литьë и металлургия)
The matters of rectification of the negative structure heredity of cast iron, which is transmitted to castings in the result of using of different burden materials at melting of cast iron in cupolas are considered.